A calibration strategy for LA-ICP-MS using isotope dilution for solid reference materials. Issue 6 (27th May 2016) - Thieleke, J. P.; Vogt, C.
Abstract : An isotope dilution method for the quantitative analysis of trace elements in biological samples and for the characterization of reference materials for the analysis of biological samples by laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-ID-MS) has been tested. Abstract : An isotope dilution method for the quantitative analysis of trace elements in biological samples and for the characterization of reference materials for the analysis of biological samples by laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-ID-MS) has been tested. Polymeric thin layers with 5–10 μm thickness containing the ID-spike and the correction standard were produced by knife application onto polyester substrates. For the ID experiments 204 Pb enriched lead was used, and bismuth served as the internal standard. The layers showed good homogeneity of the layer thickness and the distribution of added elements. For the testing of the ID method, a synthetic sample with lead and a lead containing polymer certified reference material (BAM H010) have been used. Mass fractions for lead calculated after single and double isotope dilution experiments in the test samples showed a deviation of less than 1% from the certified values.